To solve the expression 1 2/6 + 6 3/6, we can first add the whole numbers together and then add the fractions together.
1 + 2/6 = 1 + 1/3 = 3/3 + 1/3 = 4/3
6 + 3/6 = 6 + 1/2 = 12/2 + 1/2 = 13/2
Now, we have 4/3 + 13/2. To add these fractions, we need a common denominator. The least common multiple of 3 and 2 is 6.
4/3 = (4/3) * (2/2) = 8/6
13/2 = (13/2) * (3/3) = 39/6
Now that we have a common denominator, we can add the fractions:
8/6 + 39/6 = (8 + 39)/6 = 47/6
Therefore, the solution is 47/6.
Solving 1 2/6+6 3/6
1 answer